The genus Suillus Gray in the West Highland of Vietnam - Dung, Le Ba (Academia Journal of Biology, 2006)
There are 6 species belonging to the genus Suillus Gray [Suillus granulatus (L. ex Fr.) Kuntze, S. luteus (L. ex Fr.) S. F. Gray, S. bovinus (L. ex Fr.) Kuntze, S. piperatus Bull. ex (Fr.) Kuntze, S. viscidus L. ex Fr. and S. grevillei (Klotzsch.) Sing.] in the West Highland of Vietnam. 5 species [Suilus granulatus (L. ex Fr.) Kuntze, S. luteus (L. ex Fr.) S. F. Gray, S. bovinus (L. ex Fr.) Kuntze, S. piperatus Bull. ex (Fr.) Kuntze, S. viscidus L. ex Fr.] grow on soil in the pine forest. Only the species Suillus grevillei (Klotzsch.) Sing. grows on soil in the pine forest and the mixed forest. The species S. grevillei (Klotzsch.) Sing. is a new species to the West Highland macrofungi flora and may be a new species to the Vietnam macrofungi. The fruit body fleshes of these 6 species are soft, easily rotten and they are used as food.